Skin layer material for skin-core fiber, skin-core fiber containing skin layer material and preparation method of skin layer material
Through the compatibility of transesterification of PBAT and PBS, the bonding problem of PBAT fibers in the spinning process is solved, efficient and low-cost spinning processing is achieved, and the strength and spinability of the fibers are improved. It is suitable for Hot air non-woven fabric manufacturing.
Patent Information
- Application Number
- CN202411597926.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-03
AI Technical Summary
Existing PBAT fibers are prone to bond during spinning, resulting in low fiber strength, high cost, low crystallization temperature and slow crystallization rate, which limits its application in spinning and post-processing.
By modifying the compatibility of PBAT and PBS with transesterification, a PBAT/PBS cortical material with good compatibility was prepared. Combined with appropriate transesterification catalysts and process conditions, the crystallinity and dispersion of PBAT are improved, the melting point is reduced, and the melting point is improved. Spinning performance.
It realizes stable spinning processing of PBAT/PBS fibers, reduces the breaking rate and production cost, improves the strength and spinning properties of the fibers. It is suitable for hot air non-woven fabric manufacturing, and can adjust the fiber feel and adapt to different spinning equipment and Craft.
Smart Images

Figure CN119243369A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber materials, and in particular relates to a sheath-core fiber and a sheath-core fiber containing the same, and a preparation method thereof. Background Art
[0002] In order to alleviate the huge pressure on environmental protection caused by waste textiles, it is particularly important to develop biodegradable textiles. Fibers with a single fiber linear density of more than 3dtex are usually called coarse denier fibers, and fibers with a single fiber density of 1-3dtex are called fine denier fibers. The finer the fiber, the more stringent the requirements for raw materials and processes. In fact, fine denier ES fibers can have higher economic value. In spinning fine denier yarns, the quality of the slices directly affects the stability of high-speed spinning. The impurity content of the slices needs to be strictly required. Impurities such as gel particles will increase the breakage rate. Acid value, thermal degradation, water content, etc. also have a key impact.
[0003] At present, commercial products of biodegradable polymers mainly include PLA, PBAT and PBS. Polylactic acid (PLA) is an important type of polyhydroxy acid with good spinning performance. It has been widely studied in the field of fibers and nonwoven materials in recent years. However, PLA is a hard and brittle material, and the fibers made from it still feel hard. In addition, PLA is expensive, and both the skin and core components use PLA, which is costly, and further cost reduction is needed in the market.
[0004] Polybutylene adipate-terephthalate (PBAT) is a biodegradable semi-crystalline polyester with a price of about half that of PLA. It has been widely used in industries such as agricultural films and food packaging. In addition, the development and application of PBAT fibers have also attracted great attention. However, the preparation of PBAT fibers mainly adopts electrospinning, which has high production costs and low fiber strength, and the products are mostly used in medical applications.
[0005] PBAT has a melting point of about 120°C and a high molecular weight flexibility, making it suitable for the cortex of sheath-core fibers. However, PBAT is currently mainly produced by direct esterification or ester exchange, and the resulting polymer is a random copolymer with a glass transition temperature below zero, a low crystallization temperature, and a slow speed. Therefore, fiber bonding is likely to occur during the spinning process, making it impossible to wind and unwind. At the same time, during the dyeing and finishing process, bonding will also occur under high temperature conditions, resulting in differences in the feel and style of the fabric, and reduced wearing performance. In addition, during the use of incompletely crystallized products, the degree of crystallinity will be affected by the use environment, making its size, mechanical properties, etc. unstable.
[0006] Melt spinning is considered to be the most environmentally friendly fiber processing technology, but it is limited by the low crystallization temperature and slow crystallization rate of PBAT, which leads to easy adhesion between fibers during the winding process, making the spun fibers unable to be post-processed. Therefore, there is currently little research on melt-spun PBAT fibers. Summary of the invention
[0007] The purpose of the present invention is to solve the problems faced in the background technology, thereby providing a cortex material for sheath-core fiber, a biodegradable sheath-core fiber containing the same and a preparation method thereof, wherein the cortex material is PBAT modified by PBS ester exchange, so that PBAT has good compatibility with PBS and is more conducive to spinning processing.
[0008] To achieve the above-mentioned object, one aspect of the present invention provides a skin material for a sheath-core fiber, wherein the skin material is a skin PBAT / PBS material; the skin PBAT / PBS material is the product of melt blending and undergoing an ester exchange reaction of 10 to 90 parts by weight of PBAT, 10 to 90 parts by weight of PBS and an ester exchange catalyst accounting for 0.05 to 0.2 wt% of the total weight of the skin PBAT / PBS material.
[0009] In some embodiments, the transesterification catalyst is selected from one or more of stannous chloride, titanium butanediol, tetrabutyl titanate, titanium dioxide, zinc acetate and manganese acetate.
[0010] In some embodiments, the crystallinity Xc of the cortical PBAT / PBS material is greater than 30%.
[0011] In some embodiments, the dispersed size of the PBS phase in the PBAT phase in the cortical PBAT / PBS material is less than 500 nm, preferably less than 400 nm.
[0012] In some embodiments, the skin PBAT / PBS material has the following branching degree: the shear viscosity ratio at 190° C., 2000 Hz and 4000 Hz is 1.00-1.70.
[0013] In some embodiments, the PBS in the skin PBAT / PBS material has the following branching degree: the shear viscosity ratio at 190° C., 2000 Hz and 4000 Hz is 1.00-1.90, preferably 1.00-1.75, and more preferably 1.00-1.70.
[0014] In some embodiments, the tensile modulus of the skin PBAT / PBS material is greater than 350 MPa, preferably greater than 380 MPa, and more preferably greater than 400 MPa.
[0015] In some embodiments, the PBAT used in the skin PBAT / PBS material has a melt flow rate of 3 to 60 g / 10 min, preferably 3 to 50 g / 10 min, and more preferably 3 to 40 g / 10 min under the test conditions of 190° C. and 2.16 kg load.
[0016] In some embodiments, the PBS used in the skin PBAT / PBS material has a melt flow rate of 3 to 60 g / 10 min, preferably 3 to 50 g / 10 min, and more preferably 3 to 40 g / 10 min under the test conditions of 190° C. and 2.16 kg load.
[0017] In some embodiments, the skin PBAT / PBS material has a melt flow rate of 3 to 60 g / 10 min, preferably 3 to 50 g / 10 min, and more preferably 3 to 40 g / 10 min under the test conditions of 190° C. and 2.16 kg load.
[0018] In some embodiments, the acid value of the skin PBAT / PBS material is within 80 mol / T, preferably within 60 mol / T, and more preferably within 40 mol / T. The smaller the skin acid value, the less degradation during spinning and the better the spinnability.
[0019] In some embodiments, the melting point of the skin PBAT / PBS material is below 140°C, preferably below 120°C, and more preferably below 115°C. The core-skin fiber is often made into hot air nonwoven fabrics as a primary sanitary material, and the skin layer requires a low melting point material. The skin PBAT / PBS material of the present invention has a lower melting point and is suitable for hot air nonwoven fabric manufacturing.
[0020] In some embodiments, when the shear viscosity ratio of PBS is higher than 1.80, the PBS content in the skin PBAT / PBS material is no more than 50 wt %, preferably no more than 30 wt %.
[0021] In some embodiments, the preparation method of the cortical PBAT / PBS material is as follows:
[0022] PBAT and PBS are dried at 70-90° C. respectively until the water content is less than 50 ppm, and the dried PBAT, PBS and ester exchange catalyst are melt-blended and extruded using a twin-screw extruder to obtain the skin PBAT / PBS material; wherein the screw speed of the twin-screw extruder is set to 300-600 r / min, and the extrusion temperature is 160° C.-250° C.
[0023] Another aspect of the present invention further provides a biodegradable sheath-core fiber, the biodegradable sheath-core fiber comprising the following components:
[0024] Core layer material, 30 to 70 parts by weight;
[0025] 30-70 parts by weight of the above-mentioned cortical PBAT / PBS material;
[0026] The skin layer PBAT / PBS material covers the core layer material,
[0027] The core layer material can be any suitable polymer material. When the core-skin fiber is used as a disposable sanitary material, it is often made into a hot air non-woven fabric, and the core layer needs a high melting point material. In some embodiments, the core layer material is PLA, including pure PLA or a composite with PLA as the main component, preferably pure PLA. The PLA has a melt flow rate of 3 to 30 g / 10 min, preferably 5 to 20 g / 10 min, and more preferably 7 to 15 g / 10 min under the test conditions of 190°C and 2.16 kg load.
[0028] In some embodiments, the monofilament linear density of the biodegradable sheath-core fiber is 1 to 10 dtex, preferably 1 to 5 dtex, and more preferably 1 to 3 dtex.
[0029] In some embodiments, the number of breakages during spinning of the biodegradable sheath-core fiber is less than 5 times / (position·d), preferably, less than 3 times / (position·d), and more preferably less than 2 times / (position·d).
[0030] In some embodiments, the optical purity of the PLA is above 96%, preferably above 98%, and more preferably above 99%.
[0031] In some embodiments, the method for preparing the above-mentioned biodegradable sheath-core fiber comprises the following steps:
[0032] Step a: drying PBAT and PBS at 70-90° C. respectively until the water content is less than 50 ppm, and melt-blending and extruding the dried PBAT, PBS and transesterification catalyst using a twin-screw extruder to obtain the skin PBAT / PBS material; wherein the screw speed of the twin-screw extruder is set to 300-600 r / min, and the extrusion temperature is 160° C.-250° C.;
[0033] Step b: drying the core layer material and the skin layer PBAT / PBS material at 70-90° C. until the water content is less than 50 ppm; respectively sending the dried core layer material and the skin layer PBAT / PBS material into two sets of spinning systems, melting, filtering, and then inputting into the skin-core composite spinning assembly to form a biodegradable skin-core fiber with a skin-core structure.
[0034] In some embodiments, the method further comprises
[0035] Step c: the biodegradable sheath-core fiber is further subjected to one or more treatment steps of side-blowing cooling, oiling, winding, stretching, heat setting, and cutting.
[0036] In summary, the present invention has the following characteristics and beneficial effects:
[0037] (1) In the biodegradable sheath-core fiber of the present invention, the sheath material is PBAT modified by PBS ester exchange, so that PBAT and PBS have good compatibility and are more conducive to spinning processing.
[0038] (2) The skin material limits the rheological properties of the raw PBS and the modified skin material. The skin material has good spinnability and low breakage rate, and can be used to prepare 1-3 dtex fine denier ES fibers, which has practical production significance.
[0039] (3) The present invention solves the problem of easy adhesion during winding, hot stretching, curling and cutting of PBAT due to low crystallization temperature and slow crystallization rate during the process of melt spinning to staple fiber. Moreover, the present invention can adjust the cortical modulus through PBS, thereby adjusting the fiber feel and producing a series of differentiated biodegradable fiber products.
[0040] (4) The preparation method of the biodegradable sheath-core fiber provided by the present invention, as well as the controllable crystallization properties of the sheath raw material, can be adapted to the existing spinning processes of different spinning plants, and can be quickly integrated into the traditional sheath-core fiber production line of non-degradable materials, avoiding large-scale modification of existing equipment and processes, and is more conducive to biodegradable ES fiber replacement. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is an electron microscope image of the cortical PBAT / PBS material of Comparative Example 3.
[0042] Figure 2 This is an electron microscope image of the cortical PBAT / PBS material of Example 3.
[0043] Figure 3 This is an electron microscope image of the cross-section of the sheath-core fiber of Example 3. DETAILED DESCRIPTION
[0044] The present invention is further described below by means of specific embodiments. The embodiments of the present invention are only used as illustrations of the present invention and do not mean that the scope of the present invention is limited thereto.
[0045] Sources:
[0046] PBAT-1: polybutylene terephthalate adipate, melt flow rate 4.1g / 10min (under the test conditions of 190℃ and 2.16kg load), chain extender is difunctional hexamethylene diisocyanate (HDI), melting point 120℃, shear viscosity at 2000Hz at 190℃ is 265Pa.s, shear viscosity at 4000Hz is 160Pa.s, acid value 17mol / T.
[0047] PBAT-2: polybutylene terephthalate adipate, melt flow rate 10g / 10min (under test conditions of 190℃ and 2.16kg load), chain extender is difunctional hexamethylene diisocyanate (HDI), melting point 120℃, shear viscosity at 2000Hz at 190℃ is 190Pa.s, shear viscosity at 4000Hz is 115Pa.s, acid value 24mol / T.
[0048] PBS-1: polybutylene succinate, Tunhe 803S, melt flow rate 4.4 g / 10 min (under the test conditions of 190°C and 2.16 kg load), melting point 115°C, shear viscosity at 2000 Hz at 190°C is 243 Pa.s, shear viscosity at 4000 Hz is 133 Pa.s, acid value 16 mol / T.
[0049] PBS-2: polybutylene succinate, melt flow rate 4.5 g / 10 min (under the test conditions of 190°C and 2.16 kg load), melting point 115°C, shear viscosity at 2000 Hz at 190°C is 246 Pa.s, shear viscosity at 4000 Hz is 151 Pa.s, acid value 17 mol / T.
[0050] PBS-3: polybutylene succinate, melt flow rate 27 g / 10 min (under test conditions of 190°C and 2.16 kg load), melting point 113°C, shear viscosity at 2000 Hz at 190°C is 135 Pa.s, shear viscosity at 4000 Hz is 96 Pa.s, acid value 25 mol / T.
[0051] PLA-1: polylactic acid, Kobeen L130, melt flow rate 10g / 10min (under test conditions of 190℃ and 2.16kg load), melting point 176℃, shear viscosity at 2000Hz at 190℃ is 160a.s, shear viscosity at 4000Hz is 97Pa.s, optical purity 99.5%.
[0052] PLA-2: polylactic acid, Kobeen L105, melt flow rate 35g / 10min (under test conditions of 190℃ and 2.16kg load), melting point 166℃, shear viscosity at 2000Hz at 190℃ is 108a.s, shear viscosity at 4000Hz is 72Pa.s, optical purity 99.5%.
[0053] Table 1. Material information:
[0054]
[0055] The measuring method of the breaking strength and breaking elongation in the following embodiments is as follows: the test is carried out in accordance with the national standard GB / T143442008, the clamping distance is 200 mm, and the stretching speed is 200 mm / min.
[0056] The melting enthalpy (ΔHm) and crystallization temperature (Tc) were measured by PerkinElmer DSC8500 differential scanning calorimeter in a nitrogen atmosphere, and the crystallinity (Xc) was calculated by the following formula:
[0057]
[0058] ΔHm is melting enthalpy, J / g; ΔHc is cold crystallization enthalpy, J / g; a and b are the mass fractions of PLA and PBAT, respectively; ΔH0 and ΔH0' are the melting enthalpies of PBAT and PBS when they are 100% crystallized, respectively. The melting enthalpy of PBAT when it is 100% crystallized is 114 J / g, and the melting enthalpy of PBS when it is 100% crystallized is 110 J / g.
[0059] Comparative Example 1
[0060] A biodegradable sheath-core fiber is prepared according to the following steps:
[0061] Step a: Preparation of sheath-core fiber
[0062] The skin layer raw material PBAT-1 and the core layer raw material PLA-1 were dried at 80°C for 2h. The moisture content of the dried skin layer raw material PBAT-1 was 46ppm, and the moisture content of the core layer raw material PLA-1 was 48ppm. According to the weight ratio of 50:50, the dried skin layer raw material PBAT-1 and the core layer raw material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning.
[0063] The spinning process is as follows: melt spinning → side blowing cooling → oiling → winding → stretching → heat setting → cutting. The spinning process parameters are as follows: spinning speed 3700m / min, side blowing temperature 15℃, cooling air relative humidity 75%, side blowing speed 0.4m / min, stretching multiple 1.4, heat setting temperature 100℃; the number of spinneret holes on the spinneret used for spinning is 36. The maximum temperature of the extruder is controlled at 220℃, and the main speed of the extruder is 500r / min.
[0064] The spinning bonding phenomenon is serious.
[0065] Comparative Example 2
[0066] A biodegradable sheath-core fiber is prepared according to the following steps:
[0067] Step a: Preparation of cortical PBAT / PBS material
[0068] The PBAT-1 and PBS-1 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 40ppm, and the moisture content of the PBS-1 was 49ppm. Then, the PBAT-1 and PBS-1 resins were melt-blended at a weight ratio of 50:50 using a twin-screw extruder to prepare a PBAT-1 / PBS-1 material, with the screw speed set at 500r / min and the extrusion temperature at 220°C to obtain a PBAT-1 / PBS-1 material;
[0069] Step b: Preparation of sheath-core fibers
[0070] The skin material PBAT-1 / PBS-1 and the core material PLA-1 were dried at 80°C for 2h. The moisture content of the skin material after drying was 42ppm, and the moisture content of the core material was 45ppm. According to the weight ratio of 50:50, the dried skin material PBAT-1 / PBS-1 and the core material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning.
[0071] The maximum temperature of the extruder was controlled at 220° C. It was found that during melt spinning, the droplet phenomenon was serious, the spinnability was very poor, and spinning was impossible.
[0072] Comparative Example 3
[0073] A biodegradable sheath-core fiber is prepared according to the following steps:
[0074] Step a: Preparation of cortical PBAT / PBS material
[0075] The PBAT-1 and PBS-2 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 41ppm, and the moisture content of the PBS-2 was 46ppm. Then, the PBAT-1 and PBS-2 resins were melt-blended in a weight ratio of 50:50 using a twin-screw extruder to prepare the PBAT-1 / PBS-2 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain the PBAT-1 / PBS-2 material.
[0076] Step b: Preparation of sheath-core fibers
[0077] The skin material PBAT-1 / PBS-2 and the core material PLA-1 were dried at 80°C for 2h. The moisture content of the skin material after drying was 40ppm, and the moisture content of the core material was 45ppm. According to the weight ratio of 50:50, the dried skin material PBAT-1 / PBS-1 and the core material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning.
[0078] The spinning process is as follows: melt spinning → side blowing cooling → oiling → winding → stretching → heat setting → cutting. The spinning process parameters are as follows: spinning speed 400m / min, side blowing temperature 15℃, cooling air relative humidity 75%, side blowing speed 0.4m / min, stretching multiple 1.4, heat setting temperature 100℃; the number of spinneret holes on the spinneret used for spinning is 36. The maximum temperature of the extruder is controlled at 220℃, and the main speed of the extruder is 500r / min.
[0079] Comparative Example 4
[0080] A biodegradable sheath-core fiber is prepared according to the following steps:
[0081] Step a: Preparation of cortical PBAT / PBS material
[0082] The PBAT-1 and PBS-1 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 39ppm, and the moisture content of the PBS-1 was 48ppm. Then, a twin-screw extruder was used to melt-blend PBAT-1, PBS-1, and tetrabutyl titanate in a weight ratio of 90:10:0.2 to prepare the PBAT-1 / PBS-1 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain the PBAT-1 / PBS-1 material after the transesterification reaction;
[0083] Step b: Preparation of sheath-core fibers
[0084] The skin layer raw material PBAT-1 / PBS-1 and the core layer raw material PLA-1 were dried at 80°C for 2h. The moisture content of the skin layer raw material after drying was 40ppm, and the moisture content of the core layer raw material was 45ppm. According to the weight ratio of 50:50, the dried skin layer raw material PBAT-1 / PBS-1 and the core layer raw material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning. The maximum temperature of the extruder was controlled at 220°C, and the main speed of the extruder was 500r / min.
[0085] It was found that during melt spinning, the spinning sticking phenomenon was serious.
[0086] Comparative Example 5
[0087] A biodegradable sheath-core fiber is prepared according to the following steps:
[0088] Step a: Preparation of cortical PBAT / PBS material
[0089] The PBAT-1 and PBS-1 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 39ppm, and the moisture content of the PBS-1 was 48ppm. Then, a twin-screw extruder was used to melt-blend PBAT-1, PBS-1, and tetrabutyl titanate at a weight ratio of 50:50:0.2 to prepare a PBAT-1 / PBS-1 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain a PBAT-1 / PBS-1 material after an ester exchange reaction;
[0090] Step b: Preparation of sheath-core fibers
[0091] The skin layer raw material PBAT-1 / PBS-1 and the core layer raw material PLA-1 were dried at 80°C for 2h. The moisture content of the skin layer raw material after drying was 40ppm, and the moisture content of the core layer raw material was 45ppm. According to the weight ratio of 50:50, the dried skin layer raw material PBAT-1 / PBS-1 and the core layer raw material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning. The maximum temperature of the extruder was controlled at 220°C, and the main speed of the extruder was 500r / min.
[0092] It was found that during melt spinning, the droplet filament phenomenon was serious and the spinnability was very poor.
[0093] Example 1
[0094] A biodegradable sheath-core fiber is prepared according to the following steps:
[0095] Step a: Preparation of cortical PBAT / PBS material
[0096] The PBAT-1 and PBS-1 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 39ppm, and the moisture content of the PBS-1 was 48ppm. Then, a twin-screw extruder was used to melt-blend PBAT-1, PBS-1, and tetrabutyl titanate at a weight ratio of 70:30:0.2 to prepare the PBAT-1 / PBS-1 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain the PBAT-1 / PBS-1 material after the transesterification reaction;
[0097] Step b: Preparation of sheath-core fibers
[0098] The skin material PBAT-1 / PBS-1 and the core material PLA-1 were dried at 80°C for 2h. The moisture content of the skin material after drying was 40ppm, and the moisture content of the core material was 45ppm. According to the ratio of 50:50, the dried skin material PBAT-1 / PBS-1 and the core material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning. The maximum temperature of the extruder was controlled at 220°C, and the main speed of the extruder was 500r / min.
[0099] Comparative Example 6
[0100] A biodegradable sheath-core fiber is prepared according to the following steps:
[0101] Step a: Preparation of cortical PBAT / PBS material
[0102] The PBAT-1 and PBS-2 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 40ppm, and the moisture content of the PBS-2 was 42ppm. Then, a twin-screw extruder was used to melt-blend PBAT-1, PBS-2, and tetrabutyl titanate at a ratio of 90:10:0.05 to prepare the PBAT-1 / PBS-2 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain the PBAT-1 / PBS-2 material after the transesterification reaction;
[0103] Step b: Preparation of sheath-core fibers
[0104] The skin material PBAT-1 / PBS-2 and the core material PLA-1 were dried at 80°C for 2h. The moisture content of the skin material after drying was 40ppm, and the moisture content of the core material was 45ppm. According to the ratio of 30:70, the dried skin material PBAT-1 / PBS-2 and the core material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning.
[0105] The spinning process is as follows: melt spinning → side blowing cooling → oiling → winding → stretching → heat setting → cutting. The spinning process parameters are as follows: spinning speed 3500m / min, side blowing temperature 15℃, cooling air relative humidity 75%, side blowing speed 0.4m / min, stretching multiple 1.4, heat setting temperature 100℃; the number of spinneret holes on the spinneret used for spinning is 36 holes. The maximum temperature of the extruder is controlled at 220℃, and the main speed of the extruder is 500r / min.
[0106] Comparative Example 7
[0107] A biodegradable sheath-core fiber is prepared according to the following steps:
[0108] Step a: Preparation of cortical PBAT / PBS material
[0109] The PBAT-2 and PBS-2 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-2 was 40ppm, and the moisture content of the PBS-2 was 45ppm. Then, a twin-screw extruder was used to melt-blend PBAT-2, PBS-2, and titanium butanediol in a weight ratio of 80:20:0.1 to prepare a PBAT-2 / PBS-2 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain a PBAT-2 / PBS-2 material after an ester exchange reaction;
[0110] Step b: Preparation of sheath-core fibers
[0111] The skin material PBAT-2 / PBS-2 and the core material PLA-1 were dried at 80°C for 2h. The moisture content of the skin material after drying was 45ppm, and the moisture content of the core material was 46ppm. According to the ratio of 40:60, the dried skin material PBAT-2 / PBS-2 and the core material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning.
[0112] The spinning process is as follows: melt spinning → side blowing cooling → oiling → winding → stretching → heat setting → cutting. The spinning process parameters are as follows: spinning speed 3500m / min, side blowing temperature 15℃, cooling air relative humidity 75%, side blowing speed 0.4m / min, stretching multiple 1.4, heat setting temperature 100℃; the number of spinneret holes on the spinneret used for spinning is 36 holes. The maximum temperature of the extruder is controlled at 220℃, and the main speed of the extruder is 500r / min.
[0113] Example 2
[0114] A biodegradable sheath-core fiber is prepared according to the following steps:
[0115] Step a: Preparation of cortical PBAT / PBS material
[0116] The PBAT-1 and PBS-2 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 38ppm, and the moisture content of the PBS-2 was 40ppm. Then, a twin-screw extruder was used to melt-blend PBAT-1, PBS-2, and titanium butanediol at a weight ratio of 70:30:0.1 to prepare the PBAT-1 / PBS-2 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain the PBAT-1 / PBS-2 material after the transesterification reaction;
[0117] Step b: Preparation of sheath-core fibers
[0118] The skin material PBAT-1 / PBS-2 and the core material PLA-1 were dried at 80°C for 2h. The moisture content of the skin material after drying was 44ppm, and the moisture content of the core material was 41ppm. According to the ratio of 40:60, the dried skin material PBAT-1 / PBS-2 and the core material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning.
[0119] The spinning process is as follows: melt spinning → side blowing cooling → oiling → winding → stretching → heat setting → cutting. The spinning process parameters are as follows: spinning speed 4000m / min, side blowing temperature 15℃, cooling air relative humidity 75%, side blowing speed 0.4m / min, stretching multiple 1.4, heat setting temperature 100℃; the number of spinneret holes on the spinneret used for spinning is 36. The maximum temperature of the extruder is controlled at 220℃, and the main speed of the extruder is 500r / min.
[0120] Example 3
[0121] A biodegradable sheath-core fiber is prepared according to the following steps:
[0122] Step a: Preparation of cortical PBAT / PBS material
[0123] The PBAT-1 and PBS-2 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 39ppm, and the moisture content of the PBS-2 was 46ppm. Then, a twin-screw extruder was used to melt-blend PBAT-1, PBS-2, and tetrabutyl titanate at a weight ratio of 50:50:0.2 to prepare the PBAT-1 / PBS-2 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain the PBAT-1 / PBS-2 material after the transesterification reaction;
[0124] Step b: Preparation of sheath-core fibers
[0125] The skin material PBAT-1 / PBS-2 and the core material PLA-1 were dried at 80°C for 2h. The moisture content of the skin material after drying was 44ppm, and the moisture content of the core material was 45ppm. According to the ratio of 50:50, the dried skin material PBAT-1 / PBS-2 and the core material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning.
[0126] The spinning process is as follows: melt spinning → side blowing cooling → oiling → winding → stretching → heat setting → cutting. The spinning process parameters are as follows: spinning speed 3700m / min, side blowing temperature 15℃, cooling air relative humidity 75%, side blowing speed 0.4m / min, stretching multiple 1.4, heat setting temperature 100℃; the number of spinneret holes on the spinneret used for spinning is 36. The maximum temperature of the extruder is controlled at 220℃, and the main speed of the extruder is 500r / min.
[0127] Example 4
[0128] A biodegradable sheath-core fiber is prepared according to the following steps:
[0129] Step a: Preparation of cortical PBAT / PBS material
[0130] The PBAT-1 and PBS-2 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 40ppm, and the moisture content of the PBS-2 was 50ppm. Then, a twin-screw extruder was used to melt-blend PBAT-1, PBS-2, and tetrabutyl titanate in a weight ratio of 30:70:0.2 to prepare the PBAT-1 / PBS-2 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain the PBAT-1 / PBS-2 material after the transesterification reaction.
[0131] Step b: Preparation of sheath-core fibers
[0132] The skin material PBAT-1 / PBS-2 and the core material PLA-1 were dried at 80°C for 2h. The moisture content of the skin material after drying was 50ppm, and the moisture content of the core material was 43ppm. According to the ratio of 70:30, the dried skin material PBAT-1 / PBS-2 and the core material PLA-1 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning.
[0133] The spinning process is as follows: melt spinning → side blowing cooling → oiling → winding → stretching → heat setting → cutting. The spinning process parameters are as follows: spinning speed 3600m / min, side blowing temperature 15℃, cooling air relative humidity 75%, side blowing speed 0.4m / min, stretching multiple 1.4, heat setting temperature 100℃; the number of spinneret holes on the spinneret used for spinning is 36. The maximum temperature of the extruder is controlled at 220℃, and the main speed of the extruder is 500r / min.
[0134] Example 5
[0135] A biodegradable sheath-core fiber is prepared according to the following steps:
[0136] Step a: Preparation of cortical PBAT / PBS material
[0137] The PBAT-1 and PBS-3 resins were dried at 80°C for 2h, and the moisture content of the dried PBAT-1 was 40ppm, and the moisture content of the PBS-3 was 38ppm. Then, a twin-screw extruder was used to melt-blend PBAT-1, PBS-2, and stannous chloride in a weight ratio of 50:50:0.1 to prepare the PBAT-1 / PBS-3 material, and the screw speed was set to 500r / min and the extrusion temperature was 220°C to obtain the PBAT-1 / PBS-3 material after the transesterification reaction;
[0138] Step b: Preparation of sheath-core fibers
[0139] The skin material PBAT-1 / PBS-3 and the core material PLA-2 were dried at 80°C for 2h. The moisture content of the skin material after drying was 50ppm, and the moisture content of the core material was 43ppm. According to the ratio of 50:50, the dried skin material PBAT-1 / PBS-3 and the core material PLA-2 were respectively sent to different spinning systems, melted, filtered, and quantitatively input into the skin-core composite spinning assembly through a metering pump for spinning.
[0140] The spinning process is as follows: melt spinning → side blowing cooling → oiling → winding → stretching → heat setting → cutting. The spinning process parameters are as follows: spinning speed 3500m / min, side blowing temperature 15℃, cooling air relative humidity 75%, side blowing speed 0.4m / min, stretching multiple 1.4, heat setting temperature 100℃; the number of spinneret holes on the spinneret used for spinning is 36 holes. The maximum temperature of the extruder is controlled at 220℃, and the main speed of the extruder is 500r / min.
[0141] The performance results of the skin materials of Comparative Examples 1 to 7 and Examples 1 to 5 are shown in Table 2.
[0142] Table 2
[0143]
[0144]
[0145] In Comparative Example 1, the melting point of the cortex PBAT is 120°C, the melting point of the cortex PBAT / PBS in Comparative Examples 2 and 3 that has not undergone ester exchange reaction is 115°C, and in Examples 1-5 and Comparative Examples 4-7, the melting point of PBAT / PBS is further reduced to 111-113°C after the ester exchange reaction. This unexpected phenomenon is beneficial to reducing the hot air temperature when using the sheath-core fiber to prepare hot air non-woven fabrics, thereby reducing energy consumption.
[0146] The spinning and testing results of the sheath-core materials of Comparative Examples 1 to 7 and Examples 1 to 5 are shown in Table 3.
[0147] Table 3
[0148]
[0149]
[0150] According to Table 2, it can be seen from Comparative Example 1 that when pure PBAT is used as the skin layer, serious adhesion occurs during the spinning process. The spinnability is good but it cannot be applied. This is because PBAT crystallizes slowly and it is difficult to cool quickly from the melt state. At present, the art usually uses an extended cooling distance to allow PBAT to be fully cooled. For vertical melt spinning devices, it often means large-scale equipment and site modifications. Even if PBAT does not stick to the primary fiber (POY) stage by extending the cooling distance, it will still be easy to stick to the subsequent winding, hot drawing, curling and cutting processes involving high temperature and high pressure conditions.
[0151] Since PBS has a significantly faster crystallization speed than PBAT, and both PBS and PBAT belong to the polydibasic acid diol ester biodegradable polyester, they have good compatibility with PBAT and are suitable for improving the crystallization performance of PBAT and solving the problem of easy sticking. As shown in Comparative Examples 2 to 3, attempts were made to improve the adhesion of the cortical PBAT by directly adding PBS-type resins and blending with PBAT.
[0152] The present invention uses the shear viscosity ratio at 2000Hz and 4000Hz to reflect the degree of branching. The inventor found that after adding PBS-1 to Comparative Example 2, the cortical material had a serious droplet phenomenon and could not be spun. The shear viscosity ratio of the PBAT / PBS material in Comparative Example 2 was above 1.70, which was significantly higher than that of the PBAT / PBS in Comparative Example 3. This indicates that the PBAT / PBS in Comparative Example 2 has a high degree of branching. A high degree of branching will lead to obvious extrusion swelling and reduced spinnability.
[0153] In Comparative Example 3, PBS-2 was added. Although the shear viscosity ratio of the PBAT / PBS material in Comparative Example 3 was below 1.70, it was found that the spinning speed was significantly lower than that in Comparative Example 1, and the end breakage rate was significantly increased, as high as 22.0 times / (position·d), which affected normal production.
[0154] Compared with Comparative Example 3, Example 3 uses a catalyst to catalyze the ester exchange of PBAT-1 and PBS-2, and then uses the PBAT-1 / PBS-2 material after the ester exchange reaction as the cortex. The spinning process is stable and continuous, and the maximum spinning speed can reach 3800m / min. At the same time, the easy adhesion problem of the core-skin fiber in the preparation process is solved. At the same time, when preparing 1-3dtex fine denier fibers, the breakage rate is only 1.8 times / (position·d), showing excellent spinnability and high strength, which is suitable for industrial actual continuous production. Further, the electron microscope images of the cortex PBAT / PBS materials of Example 3 and Comparative Example 3 are as follows: Figure 1 , 2 As shown, after ester exchange, the dispersion size of the PBS phase in the PBAT phase is significantly reduced to below 500nm, while the dispersion effect of the cortical PBAT / PBS material in Comparative Example 3 is at the micron level. The inventors speculate that although PBS and PBAT have good compatibility, there may still be differences in compatibility between the two due to molecular structure and other reasons, and the compatibility of PBAT and PBS is improved after esterification.
[0155] According to Example 1 and Comparative Example 5, the shear viscosity ratio of the PBS-1 used is relatively high. When the PBS-1 content is higher than 50%, the shear viscosity ratio of the PBAT / PBS material is higher than 1.70, the droplet silk is serious, and the spinnability is very poor. When the PBS-1 content does not exceed 30%, the shear viscosity ratio of the PBAT / PBS material is lower than 1.70, and the spinnability is good.
[0156] In addition, it can be seen from Examples 3 and 5 that when the shear viscosity ratio of PBS is low, the melting point of the skin layer is lower and the strength of the skin-core fiber decreases.
[0157] It can be seen from Examples 1 to 5 that when preparing PBAT / PBS, a PBS with a shear viscosity ratio of less than 1.70 is selected, and an ester exchange catalyst is added. When the obtained PBAT / PBS material is used as the sheath layer, the spinning process can be stable and continuous, and the maximum spinning speed can reach 3500 m / min. It is expected that the sheath-core fiber will not stick together during the preparation process. When preparing 1-3 dtex fine denier fibers, the breakage rate is only 2.0 times / (position·d), respectively, showing excellent spinnability and suitable for actual industrial continuous production.
[0158] The sheath-core spinning and raw material testing results of Comparative Examples 1, 6-7 and Examples 2-4 are shown in Table 4.
[0159] Table 4
[0160]
[0161] It can be seen from the above table that when the PBS-2 addition amount is 10%, the crystallinity of the cortex increases to 22.5%, which is not much improved and still sticks. Continuing to increase the PBS-2 addition amount until the crystallinity increases to more than 30% can effectively avoid adhesion.
[0162] In addition, PBS can be used to control the crystallization temperature and speed of the cortex to adapt to different spinning equipment and processes, especially for cooling tunnels of different lengths or cooling methods, and the appropriate crystallization performance can be adjusted to adapt. At the same time, by adjusting the content of PBS in the cortex, adjusting the crystallinity of the cortex material, adjusting the modulus, adjusting the hardness of the fiber, and thus adjusting the feel, a solution is provided for manufacturing biodegradable fibers with different feels.
[0163] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A cortex material for a sheath-core fiber, characterized in that: The cortex material is a cortex PBAT / PBS material, The skin PBAT / PBS material is a product obtained by melt blending 10 to 90 parts by weight of PBAT, 10 to 90 parts by weight of PBS and 0.05 to 0.2 wt% of an ester exchange catalyst accounting for the total weight of the skin PBAT / PBS material and undergoing an ester exchange reaction.
2. The skin material according to claim 1, characterized in that: The transesterification catalyst is selected from one or more of stannous chloride, titanium butanediol, tetrabutyl titanate, titanium dioxide, zinc acetate and manganese acetate.
3. The skin material according to claim 1 or 2, characterized in that: The crystallinity Xc of the cortical PBAT / PBS material is above 30%; Preferably, the dispersion size of the PBS phase in the PBAT phase in the skin PBAT / PBS material is less than 500 nm, more preferably less than 400 nm; Preferably, the skin PBAT / PBS material has the following branching degree: the shear viscosity ratio at 190°C, 2000Hz and 4000Hz is 1.00-1.70; Preferably, the PBS in the skin PBAT / PBS material has the following branching degree: the shear viscosity ratio at 190°C, 2000 Hz and 4000 Hz is 1.00 to 1.90, preferably 1.00 to 1.75, more preferably 1.00 to 1.70; Preferably, the tensile modulus of the skin PBAT / PBS material is 350 MPa or more, preferably 380 MPa or more, and more preferably 400 MPa or more; Preferably, the PBAT used in the skin PBAT / PBS material has a melt flow rate of 3 to 60 g / 10 min, preferably 3 to 50 g / 10 min, and more preferably 3 to 40 g / 10 min under the test conditions of 190° C. and 2.16 kg load; Preferably, the PBS used in the skin PBAT / PBS material has a melt flow rate of 3 to 60 g / 10 min, preferably 3 to 50 g / 10 min, and more preferably 3 to 40 g / 10 min under the test conditions of 190° C. and 2.16 kg load; Preferably, the skin PBAT / PBS material has a melt flow rate of 3 to 60 g / 10 min, preferably 3 to 50 g / 10 min, and more preferably 3 to 40 g / 10 min under the test conditions of 190° C. and 2.16 kg load; Preferably, the acid value of the skin PBAT / PBS material is within 80 mol / T, preferably within 60 mol / T, more preferably within 40 mol / T; Preferably, the melting point of the skin PBAT / PBS material is below 140°C, preferably below 120°C, and more preferably below 115°C.
4. The skin material according to any one of claims 1 to 3, characterized in that: When the shear viscosity ratio of PBS is higher than 1.80, the PBS content in the skin layer PBAT / PBS material does not exceed 50 wt %, preferably does not exceed 30 wt %.
5. The skin material according to any one of claims 1 to 4, characterized in that: The preparation method of the cortical PBAT / PBS material is as follows: PBAT and PBS are dried at 70-90° C. respectively until the water content is less than 50 ppm, and the dried PBAT, PBS and ester exchange catalyst are melt-blended and extruded using a twin-screw extruder to obtain the skin PBAT / PBS material; wherein the screw speed of the twin-screw extruder is set to 300-600 r / min, and the extrusion temperature is 160° C.-250° C.
6. A biodegradable sheath-core fiber, characterized in that: The biodegradable sheath-core fiber comprises the following components: Core layer material, 30 to 70 parts by weight; The skin material according to any one of claims 1 to 5, 30 to 70 parts by weight; The skin layer material covers the core layer material.
7. The biodegradable sheath-core fiber according to claim 6, characterized in that: The core layer material is PLA, and the PLA has a melt flow rate of 3 to 30 g / 10 min, preferably 5 to 20 g / 10 min, and more preferably 7 to 15 g / 10 min under the test conditions of 190° C. and 2.16 kg load; Preferably, the optical purity of the PLA is above 96%, preferably above 98%, and more preferably above 99%.
8. The biodegradable sheath-core fiber according to claim 6 or 7, characterized in that: The monofilament linear density of the biodegradable sheath-core fiber is 1 to 10 dtex, preferably 1 to 5 dtex, more preferably 1 to 3 dtex; Preferably, the number of breakages during spinning of the biodegradable sheath-core fiber is less than 5 times / (position·d), preferably, less than 3 times / (position·d), and more preferably, less than 2 times / (position·d).
9. A method for preparing the biodegradable sheath-core fiber according to any one of claims 6 to 8, characterized in that: The steps include: Step a: drying PBAT and PBS at 70-90° C. respectively until the water content is less than 50 ppm, and melt-blending and extruding the dried PBAT, PBS and transesterification catalyst using a twin-screw extruder to obtain the skin PBAT / PBS material; wherein the screw speed of the twin-screw extruder is set to 300-600 r / min, and the extrusion temperature is 160° C.-250° C.; Step b: drying the core layer material and the skin layer PBAT / PBS material at 70-90° C. until the water content is less than 50 ppm; respectively sending the dried core layer material and the skin layer PBAT / PBS material into two sets of spinning systems, melting, filtering, and then inputting into the skin-core composite spinning assembly to form a biodegradable skin-core fiber with a skin-core structure.
10. The method for preparing biodegradable sheath-core fiber according to claim 9, characterized in that: The method further comprises Step c: the biodegradable sheath-core fiber is further subjected to one or more treatment steps of side-blowing cooling, oiling, winding, stretching, heat setting, and cutting.
